New designs of foot prostheses with use of high-temperature silicone - Solntseva, Irina; Khmelevskaya, Iryna; Grishko, Yevgene; Belevtsova, Lyudmila; Yutkin, Vladimir (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
New designs of foot prostheses made of unicomponent domestic high-temperature silicon Termosil were examined. Application of these more cosmetic and hygienic prostheses in prosthetic management of patients with foot amputation at different levels made it possible to provide uniform redistribution of local pressure, improve the rhythm and smoothness of walking as well as decrease its power consumption.